Metal‐Containing Pharmacophores in Molecularly Targeted Anticancer Therapies and Diagnostics. Issue 12 (15th November 2016) - Yang, Mu; Bierbach, Ulrich
Abstract : Molecularly targeted therapeutic agents make up an important class of oncology drugs that are used either alone, or in combination with classical cytotoxic agents, to combat many solid tumors and hematological cancers. Their targets in cancer cells are proteins that are encoded by oncogenes, which regulate cell growth, survival, and proliferation. These include a number of signal‐transducing and angiogenesis‐related kinases, hormone receptors, and certain cell‐surface antigens. Targeting of cancer cells harboring oncogenic molecular targets with precision medicines, while sparing the vast majority of normal healthy cells, has led to promising new treatments for cancer patients. Molecularly targeted therapeutic agents promise higher efficacy and weaker side effects than the traditional cytotoxic chemotherapies. Simple metal complexes and metal–organic hybrid agents have been the subjects of investigation for many years since the success of cisplatin in treating genitourinary cancers, but their applications in targeted therapies remain underexplored. In this review we highlight the development of metal‐based targeted cancer therapeutic agents with unique structures and functions. These strategies provide exciting opportunities for discovering new therapeutic and diagnostic agents for clinical uses. Abstract : Metal‐containing pharmaceuticals have a long history of applications in cytotoxic chemotherapies. Treatment of malignant disease in the postgenomic era has long moved beyond the use of indiscriminate cell poisons. Inorganic elements are now beginning to play exciting new roles in the design of smarter, molecularly targeted therapeutic agents and diagnostics.